Detection and In Silico Study of Neochlorogenic Acid from Rhizophora apiculata Stem Bark Extract as HBV Replication Inhibitors - Khalil, Muhammad; Dwitya, Yonadiah (Postgraduate, University of Mataram, 2023)
This study aims to detect and characterize the presence of neochlorogenic acid in Rhizophora apiculata stem bark extract and to examine its potential as an inhibitor of Hepatitis B virus (HBV) replication with in silico approach. This explorative descriptive study used liquid chromatography-mass spectrometry (LC-MS/MS) analysis to detect the content of neochlorogenic acid, and an in silico study through molecular docking analysis using the blind docking technique to test its potential to inhibit HBV replication. LCMS/MS results showed that the neochlorogenic acid was present in R. apiculata stem bark extract which was detected with a peak at 3.94 retention time, and fragment ion with a m/z value of 355.1029. The docking analysis results showed that neochlorogenic acid forms a binding site that is relatively similar to the reference ligand to the HBV capsid protein, involving amino acid residues PHE 23, PRO 25, PHE 110, TYR 118, TRP 102, ILE 139, LEU 140, and SER 141, with binding affinity score -6.3 kcal/mol. Therefore, based on the results of this study, it can be concluded that neochlorogenic acid derived from stem bark extract of R. apiculata has the potential to be used as an alternative treatment for hepatitis B virus infection.Â